2012
DOI: 10.1038/ncomms2259
|View full text |Cite
|
Sign up to set email alerts
|

Distinct modes of DNA accessibility in plant chromatin

Abstract: The accessibility of DNA to regulatory proteins is a major property of the chromatin environment that favours or hinders transcription. Recent studies in flies reported that H3K9me2-marked heterochromatin is accessible while H3K27me3-marked chromatin forms extensive domains of low accessibility. Here we show that plants regulate DNA accessibility differently. H3K9me2-marked heterochromatin is the least accessible in the Arabidopsis thaliana genome, and H3K27me3-marked chromatin also has low accessibility. We s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
57
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 51 publications
(60 citation statements)
references
References 59 publications
3
57
0
Order By: Relevance
“…For the chromatin digestion, PCR signals of the two heterochromatic TE genes remained nearly constant while PCR signals of the two active genes dropped rapidly, confirming our hypothesis of differences between heterochromatin regions and active genes. This is in agreement with genome-wide profiles (Shu et al, 2012) and establishes these regions as insensitive and sensitive controls for future assays. Interestingly, the sensitivity of the two PcG-targeted genes AG and FT seemed to be between the TE genes and the active genes.…”
Section: Analysis Of Digested Dna By Pcrsupporting
confidence: 85%
See 4 more Smart Citations
“…For the chromatin digestion, PCR signals of the two heterochromatic TE genes remained nearly constant while PCR signals of the two active genes dropped rapidly, confirming our hypothesis of differences between heterochromatin regions and active genes. This is in agreement with genome-wide profiles (Shu et al, 2012) and establishes these regions as insensitive and sensitive controls for future assays. Interestingly, the sensitivity of the two PcG-targeted genes AG and FT seemed to be between the TE genes and the active genes.…”
Section: Analysis Of Digested Dna By Pcrsupporting
confidence: 85%
“…As an example, the chromatin sensitivity was analyzed for two silent transposable element (TE) genes (Ta2 and Cinful-like) and two active genes (GAPDHa and ACTIN7 [ACT7]) in Arabidopsis. We and others have shown that transcription is generally associated with accessible chromatin (Weil et al, 2004;Boyle et al, 2008;Bell et al, 2010;Shu et al, 2012;Zhang et al, 2012). Thus, we predict that the two TE genes should be much less sensitive to DNase I than the two active genes and, therefore, can be used as insensitive and sensitive controls in future assays.…”
Section: Analysis Of Digested Dna By Pcrmentioning
confidence: 66%
See 3 more Smart Citations